Impact of the group intervention "Accept Voices©" for the management of auditory hallucinations. (September 2020) - Langlois, T.; Sanchez-Rodriguez, R.; Bourcier, A.; Lamy, P.; Callahan, S.; Lecomte, T.
Hightlights: The group Accept Voices appear to diminish the intensity of auditory hallucinations in participants. Acceptance and mindfulness techniques seem to facilitate the acceptance of voices. The Accept voices group decreases depression and anxiety symptoms post-therapy. A short group therapy for voice management significantly improves coping with auditory hallucinations. Abstract: Aim of the study: The objective of this study was to evaluate the potential impact of a third wave CBT group intervention for the management of auditory hallucinations in patients with schizophrenia. Method: 38 patients with schizophrenia presenting with auditory hallucinations, followed in mental health services, participated in six sessions of a group based on acceptance and engagement therapy (ACT). The study followed a repeated single case experimental design (type A-B-A) based on the principle of a control phase followed by an intervention phase and a follow-up phase of similar duration. The various measurements were administered during the control phase, at pre-/post-group and six weeks after the last group session. Results: The results show a significant decrease in auditory hallucinations, as measured by the PSYRATS scale, during the treatment and follow-up phase, compared to the control phase. In addition, the participants saw significant reductions in depressive and anxious symptomatology (assessed with CDSS and SEAS), and increases in coping and acceptance in regards to voices (assessed using a study scale and VAAS). The level of Malevolence beliefs about voices (measured with BAVQ-R) also decreased significantly. Conclusions: A brief group intervention based acceptance show promise in the reduction of the intensity of auditory hallucinations, depression and anxiety in patients with schizophrenia, while improving their acceptance.